Hematopoietic Cytokine Gene Duplication in Zebrafish Erythroid and Myeloid Lineages - Oltova, Jana; Svoboda, Ondrej; Bartunek, Petr (Frontiers in Cell and Developmental Biology, 2018)
Hematopoiesis is precisely orchestrated process regulated by the activity of hematopoietic cytokines and their respective receptors. Due to an extra round of whole genome duplication during vertebrate evolution in teleost fish, zebrafish has yielded two paralogs of many important genes and genes involved in hematopoiesis. Importantly, these duplication events brought an increased level of complexity in such cases, where both ligands and receptors have been duplicated in parallel. Therefore, precise understanding of binding specificities between duplicated ligand-receptor signalosomes as well as the understanding of their differential expression provides​ an important basis for future studies to better understand the role of duplication of these genes. However, although many recent studies in the field have partly addressed functional redundancy or sub-specialization of some of those duplicated paralogs, this information remains to be scattered over many publications and unpublished data. Therefore, the focus of this review is to provide an overview of recent findings in the zebrafish hematopoietic field regarding activity, role, and specificity of some of the hematopoietic cytokines with emphasis on crucial regulators of the erythro-myeloid lineages.